The Souls of Muslim Folk: The “Obama Phenomenon” and the Paradoxes of Paranoid anti-Multiculturalism (American Journal of Islam and Society, 2012)
The current debate on the vices of multiculturalism and the merits of integration, of problematizing cultural difference, appears to miss important lessons from recent history in the treatment of minorities. In this paper, I start by questioning the celebration of Barack Obama’s election as a “breakthrough” for multicultural inclusiveness. I argue that the “Obama phenomenon” highlights the limits of democratic inclusiveness and sheds light on the traumatic experience of African Americans, who have been victimized precisely for seeking to assimilate. European Jews, especially in Germany, could not be accused of any reluctance to integrate either, and their contributions to European culture are legendary. But they also suffered grievously for their pains. Thus when the same xenophobic political trends traditionally hostile to the integration of minorities begin to vociferously demand that Muslims should integrate, this must be seen as a warning that we may be heading toward a very dark phase of race relations in the West.